Proceedings of the 9th European Conference on Games Based Learning : ECGBL 2015, Nord-Trondelag University College, Steinkjer, Norway, 8-9 October 2015 /: ECGBL 2015, Nord-Trondelag University College, Steinkjer, Norway, 8-9 October 2015. ([2015]) - Unknown
No abstract available